Innovative approaches to growing grain crops in the Southern Steppe of Ukraine - Antonina Drobitko; Tetiana Kachanova; Nataliia Markova; Nataliia Nikonchuk (Наукові горизонти)
The aim of the study was to analyse the impact of innovative approaches to cereal cultivation in the Southern Steppe of Ukraine. The study used the latest plant varieties, efficient irrigation systems and biological products to increase crop yields and resilience. The wheat varieties used were Stepova 1 and Dniprovska 1, as well as Pivdennyi 1 barley, which are highly resistant to drought and high temperatures. Drip and sub-surface irrigation systems were used, as well as bio-fertilisers and organic composts to improve soil structure and increase soil fertility. The main results of the study showed that wheat yields in the experimental groups reached 5.2-5.7 tonnes/ha, which is 1.8-1.9 tonnes/ha more than in the control groups. Water consumption in the experimental groups was reduced by 35-40%, and the cost of plant protection products by 45-50%. The protein content of wheat in the experimental groups was 14-15% and the fibre content was 30-32%, while in the control groups it was 11-12% and 25-27%, respectively. Soil analysis in the experimental groups showed higher levels of nitrogen, phosphorus and potassium, which indicates the effectiveness of biofertilisers. In addition, the use of biological products helped to reduce the chemical load on the environment. The results obtained indicate a significant increase in productivity, reduced resource use and improved environmental sustainability with the introduction of innovative methods of growing crops in this region, which is important for ensuring food security and economic development in Ukraine